Ad Hoc Board's Ethics and Conduct Code Violation in Bolaang Mongondow General Election Commissions (KPU) - Ermawati Putri, Ni Made Desika (Lex Scientia Law Review, 2021)
The purpose of this study was to determine the implementation of repressive and preventive actions of the Ad Hoc board’s Ethics and Conduct Code in Bolaang Mongondow KPU. The research method used was empirical legal research methods, the data were from primary and secondary data with data collection techniques used were documents study and interview. The data were analyzed using qualitative data analysis, where all collected data were analyzed, connected into one another, and presented descriptively and systematically. Based on the study results, it is known that the repressive and preventive mechanism of the Ethics and Conduct Code of Ad Hoc Board of Bolaang Mogondow KPU in organizing Election for the Governor and Deputy Governor of North Sulawesi in 2020 had been carried out in accordance with statutory regulations. There were 5 (five) cases of Ethics and Conduct Code violations carried out by the Ad Hoc Board within the Bolaang Mongondow KPU.